PENGARUH LAMA PERENDAMAN MENGGUNAKAN CUKA SAGUER TERHADAP PENINGKATAN KUALITAS FISIK DAGING ENTOK (Chairina moschata) - Jengel, Erlita N.; Sondakh, E. H.B.; Ratulangi, F. S.; Palar, C. K.M. (Universitas Sam Ratulangi, 2016)
THE EFFECT OF MARINATING TIME USING CUKA SAGUER ON PHYSICAL QUALITY INCREASING OF ENTOK MEAT (Chairina Moschata). This study aims to determine of physical quality of entok meat after marinating with cuka saguer. Cuka saguer using to soak meat in this research was obtained from fermentated yield of fluid from enau tree. The marinated meat in this research was entok meat. This experiment was arranged in a completely randomized design consisted of five treatments as followed R0 entok meat was without marinated , R1 entok meat was marinated for 20 minutes, R2 entok meat was marinated for 40 minutes, R3 entok meat was marinated for 60 minutes, R4 entok meat was marinated for 80 minutes and each treatment was conducted four times replication. If occur significant in analysis of variance so the average comparing was followed by DMRT test. The result showed The marinated entok meat using cuka saguer was significantly on pH and water holding capacity (WHC), while texture of meat no significant. In conclusion, the soaking time for 20 minutes with cuka saguer can be used to soak entok meat because able to maintain texture of meat and to increase WHC at the condition of pH normal. Â Keywords: entok meat, cuka saguer, physical quality of meat